Negotiating Professionalism in Montessori Schools: Organizational Culture and Professional Development Among Generation Z Employees - Rita Kurnia; Daviq Chairilsyah; Kartika Sari; Erma Roza; Rionar Rambe; Riza Purnama Sari; Musaroh Musaroh (South Sulawesi Education Development, 2026)
Educational organizations increasingly employ younger workers who are often classified as Generation Z, yet little is known about how such employees negotiate work values within value-based school cultures. In this study, Generation Z functions as a sampling context rather than an explanatory variable, and no intergenerational comparison is intended. This study examined how younger employees within this sampling context construct professionalism in two Montessori schools in Pekanbaru, Indonesia, and how educational-management practices shape their professional development. A qualitative multiple-case design involved 10 employees aged 22–29 years, comprising eight teachers and two administrative staff; the empirical analysis used participant interview excerpts, critical incidents, a 12-code analytical framework, within-case analysis, cross-case comparison, and negative/deviant case examination. Four themes were identified. Structured professional autonomy described agency as meaningful when paired with competence, clear boundaries, trust, and accountability. Internalization of Montessori purpose showed movement from institutional rules toward professional judgment oriented to educational purpose and children’s needs. Developmental feedback and mentoring supported prepared-adult formation when they promoted reflection, competence, and self-regulation, whereas excessive monitoring could reduce initiative. Negotiated accountability captured how employees balanced agency with consequences for children, colleagues, parents, and the organization. Cross-case analysis showed that School A emphasized role clarity, coordination, and procedural reliability, whereas School B emphasized trust, reflective mentoring, and professional judgment. Integratively, the findings support negotiated professionalism as a developmental process linking agency, organizational values, professional learning, and responsibility. Montessori schools should therefore stage autonomy and feedback according to demonstrated competence, role boundaries, and decision risk rather than presumed generational preference.